2010
DOI: 10.1016/j.ajog.2010.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the transcriptome of chorioamniotic membranes at the site of rupture in spontaneous labor at term

Abstract: OBJECTIVE The purpose of this study was to compare the transcriptome between the site of membrane rupture and the chorioamniotic membranes away from the site of rupture. STUDY DESIGN The transcriptome of amnion and chorion (n =20 each) from and distal to the site of rupture from women with spontaneous labor and vaginal delivery at term after spontaneous rupture of membranes was profiled with Illumina HumanHT-12 microarrays. Selected genes were validated with the use of quantitative reverse transcription–poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 114 publications
1
75
0
1
Order By: Relevance
“…These changes would require large-scale transcriptional reprogramming, which can be carried out, at least in part, by miRNA-regulation. Nhan-Chang et al [12] showed gene expression differences between the amnion and the choriodecidua at both the rupture as well as non-rupture sites, whereas within each fetal membrane individually, only the choriodecidua showed gene expression differences between the rupture and non-rupture sites. These results are in accordance with the miRNA expression patterns in our study, and support the concept that the altered gene expression in fetal membranes in the rupture zone could be due to altered miRNA expression patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes would require large-scale transcriptional reprogramming, which can be carried out, at least in part, by miRNA-regulation. Nhan-Chang et al [12] showed gene expression differences between the amnion and the choriodecidua at both the rupture as well as non-rupture sites, whereas within each fetal membrane individually, only the choriodecidua showed gene expression differences between the rupture and non-rupture sites. These results are in accordance with the miRNA expression patterns in our study, and support the concept that the altered gene expression in fetal membranes in the rupture zone could be due to altered miRNA expression patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal membranes specimens were collected within 1-2 hours of delivery. After visual identification of the rupture zone (Figure 1) as done previously by Nhan-Chang et al [12], the two adherent fetal membranes (amnion and choriodecidua) were separated/ teased apart from the rupture tear line. A piece of membrane tissue (~ 2cm 2 ) spanning the rupture site was dissected sharply from both the amnion as well as the choriodecidua, constituting the rupture zone amnion (RZA) and rupture zone choriodecidua (RZC) samples, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…There is compelling evidence that physiologic parturition is associated with cellular and molecular signatures of inflammation in the chorioamniotic membranes [28,9196], myometrium [18,20,22,23,2527,30,93,96102], and cervix [19,21,24,93,96,103–107]. Indeed, the participation of chemokines and pro-inflammatory cytokines [108–126], eicosanoids [99,127137] and lipooxygenase arachidonate products [138–140] in physiologic labor is well established.…”
Section: Discussionmentioning
confidence: 99%
“…Increased concentrations of these cytokines have been documented during labor in different compartments, including umbilical cord blood, amniotic fluid and peripheral maternal blood 3, 11, 16, 38 . Choriodecidual cells may be a major source for these signals.…”
Section: Discussionmentioning
confidence: 99%